Hubungan Antara iklim Organisasi Dengan Work Life Balance Pada Perawat Wanita Yang Sudah Menikah Di RSUD Padang Panjang - Lathifah Rusydah; Isna Asyri Syahrini; Sari Rahmadani (Indonesian Journal of Innovation Science and Knowledge, 2026)
This study aims to determine the relationship between organizational climate and work-life balance among married female nurses at Padang Panjang Regional General Hospital. The independent variable in this study is organizational climate and the dependent variable is work-life balance. The measuring instruments used in this study are the organizational climate scale and the work-life balance scale. The sample selection technique in this study was a simple random sampling technique. The sample in this study was 88 married female employees at Padang Panjang Regional General Hospital. Validity and reliability tests in this study used the Cronbach's alpha technique. The results of the validity coefficient on the organizational climate scale ranged from 0.326 to 0.843. The results of the validity coefficient on the work-life balance scale ranged from 0.334 to 0.893. With a reliability coefficient of organizational climate of 0.944 and on the work-life balance scale of 0.955. Based on data analysis, the correlation between organizational climate and work-life balance was obtained at r = 0.583 with a significance level of p = 0.000, indicating a positive and moderate relationship between organizational climate and work-life balance among married nurses at Padang Panjang Regional Hospital. This positive correlation means that the higher the organizational climate, the higher the work-life balance, and conversely, the lower the organizational climate, the lower the work-life balance.